Administração estratégica do capital de giro e supply chain finance: um estudo exploratório de empresas e instituições financeiras que adotaram a ferramenta - Simões, Alexandre Cracovsky de Arruda (2022)
According to the Global Trade Finance Market (2022), about 80% to 90% of world trade depends on trade financing, which includes trade credit and guarantees. In Brazil during the month of June 2022, c. R$ 175 billion of anticipation on accounts receivables were made (Bacen, 2022). Working capital is often despised in academia, but of increasing attention in the management of the cash of companies. In the management of accounts payable and accounts receivables, companies take loans from their suppliers and lend to their customers, thus creating a trade credit parallel to the flow of goods. Smaller companies tend to pay very high interest rates, which increase their financial costs, while companies with higher credit ratings benefit from low interest rates provided by banks. Supply Chain Finance (SCF) is a solution that through the buyer's credit rating, with the support of technology and processes, seeks to reduce the costs of transactions between buyer and supplier and optimize the cash cycle, generating liquidity for both parties. Data from the Bis Bulletin (2020) indicate that total trade credit has its volume of around 20% of World GDP in the last 25 years, or equivalent to c. US$ 17 trillion in 2020. Commercial banks are adopting SCF platforms and expect additional growth in this space. The International Chamber of Commerce (2020) survey shows that 64% of global banks offer SCF platforms, compared to just 13% of local banks and 38% of regional banks. In Brazil, the solution is new for some companies and financial institutions. A growing number of banks and fintechs have increased attention in trade credit solutions, enabling the SCF to be more widespread in the coming years. The methodology applied in this study was that of an exploratory study with a qualitative approach to data collection, based on semi-structured in-depth interviews with individuals considered influential and/or well-informed in the SCF. The result was a report with the analysis of the respondents' answers in (i) performance indicators of working capital, which we can highlight the transaction volume, penetration in the supplier base and recurrence of the use of the solution. (ii) implementation of the SCF: motivations, convictions, technology, and headcount necessary, where the main motivation was predominantly headed by the financial institution and with dubious convictions among the teams before the implementation, needing to go through an educational process. Differently than expected, it was also identified that additional investments in technology or headcount by 9 companies were irrelevant. (iii) financial impacts of the program from the views of the buyer, where increases in payment terms were found from 30 days to more than 150 days, generating relevant cash releases such as R$ 2.6 billion and R$ 700 million in the companies of respondent B and R$ 650 million in respondent C's company, (b) supplier, with emphasis on savings in reduction in financial fees in receivables anticipation operations from 4% per month to 0.72% per month, equivalent to a positive impact of 9% on the company’s operating margin and (c) financial institution, which received fees on transactions, in addition to the possibility of expanding its offer of financial products to the buyer and its suppliers. (iv) non-financial benefits found and success factors for solution growth, with emphasis on the increased commercial relationship between the parties involved. It was also worth mentioning the use of the solution as an ESG (Environmental, Social and Governance) practice, where the buyer offered the solution as a way of low-rate financing for its small and medium suppliers and absorbing transaction fees. Among the critical success factors main takeaways is to have a buyer with high credit rating, as well as engage the areas of the company involved: commercial, purchasing, treasury and IT.